2021
DOI: 10.14309/ctg.0000000000000416
|View full text |Cite
|
Sign up to set email alerts
|

Specific Plasma MicroRNA Signatures in Predicting and Confirming Crohn's Disease Recurrence: Role and Pathogenic Implications

Abstract: INTRODUCTION: MicroRNAs (miRNAs) are important epigenetic regulators in Crohn's disease (CD); however, their contribution to postoperative recurrence (POR) is still unknown. We aimed to characterize the potential role of miRNAs in predicting POR in patients with CD and to identify their pathogenic implications. METHODS: Of 67 consecutively operated patients with CD, we included 44 with pure ileal CD. Peripheral blood samples were taken before surgery and during follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…It has been shown that elevated levels of miR-21-5p in the stool of IBD patients could be a guide for the noninvasive clinical diagnosis of IBD ( Zhou et al, 2021b ). It has been demonstrated that miR-93-5p is upregulated before surgery and downregulated in relapsed CD patients ( Moret-Tatay et al, 2021 ). Wang et al found that the lncRNA MEG3 could improve ulcerative colitis by upregulating miR-98-5p-Sponed IL-10 ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that elevated levels of miR-21-5p in the stool of IBD patients could be a guide for the noninvasive clinical diagnosis of IBD ( Zhou et al, 2021b ). It has been demonstrated that miR-93-5p is upregulated before surgery and downregulated in relapsed CD patients ( Moret-Tatay et al, 2021 ). Wang et al found that the lncRNA MEG3 could improve ulcerative colitis by upregulating miR-98-5p-Sponed IL-10 ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…They share analogous characteristics, such as intermittent, chronic, and/or progressive inflammation and features specific to each such as transmural inflammation of the gastrointestinal wall (from the mouth to the anus) in CD and inflammation limited to the colon and rectal mucosa in UC [ 5 ]. Although the etiopathogenesis of IBD remains unknown, the disease appears to be a dysregulated immune response to unknown triggers in genetically predisposed patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its complexity, it is an interesting factor that needs to be explored in detail in other specific reviews. On the other hand, noncoding RNAs, especially microRNAs, represent the most studied epigenetic mechanism in IBD, and many reviews have dealt with this topic [ 6 , 19 ]. Therefore, we have focused on describing in detail other more novel and less studied epigenetic mechanisms in IBD.…”
Section: Introductionmentioning
confidence: 99%
“…4 Recent molecular research has shown that between the epigenetic mechanisms, microRNAs (miRNAs) emerge as important factors in the physiopathology of IBD. 1,5 miRNAs are evolutionarily conserved, endogenous, single-stranded, non-coding RNAs that bind to the 3 0 untranslated region (UTR), 5' UTR, or partially translated region of a target mRNA, which usually inhibit mRNA expression. 1 MiRNAs play an important biological role as regulators of cell function and homeostasis, so their impaired activities are linked to disease, as is the case for UC.…”
Section: Introductionmentioning
confidence: 99%